ULTRASONOGRAPHIC IMAGING FOR EARLY PREGNANCY DIAGNOSIS IN MARES - BANSAL, R S; PAL, YASH; PAREEK, P K (The Indian Journal of Animal Reproduction, 2023)
The study was planned to detect pregnancy in mares using ultrasound machine with 7 .5 MHz linear rectal probe. The presence of embryo was observed as early as day 10 post insemination using this technique. The conceptus was observed spherical in shape up to day 15 of gestation in mares. This technique of pregnancy diagnosis is less time consuming, reliable, animal friendly, safe and sensitive. Hence, ultrasound can be used as a tool for early pregnancy diagnosis in mares.